Assemblies of Functional Peptides and Their Applications in Building Blocks for Biosensors - de la Rica, Roberto (2011)
We highlight our recent applications of functional peptide nanotubes, self-assembled from short peptides with recognition elements, as building blocks to develop sensors. Peptide nanotubes with high aspect ratios are excellent building blocks for directed assembly into device configurations, and their combining structures with the nanometric diameters and the micrometric lengths enables to bridge the nano-world and the micro-world.